Teologia e Literatura Russa: Editorial - Villas Boas, Alex; Manzatto, Antonio; Fernandes, Marcio; Zak, Lubomir (TEOLITERARIA - Revista de Literaturas e Teologias, 2018)
Teologia e Literatura Russa: Editorial